2020
DOI: 10.1002/pne2.12033
|View full text |Cite
|
Sign up to set email alerts
|

New techniques, new challenges—The dilemma of pain management for less invasive surfactant administration?

Abstract: Recent years have seen the increasing use of noninvasive respiratory support in preterm infants with the aim of minimizing the risk of mechanical ventilation and subsequent bronchopulmonary dysplasia. Respiratory distress syndrome is the most common respiratory diagnosis in preterm infants, and is best treated by administration of surfactant. Until recently, this has been performed via an endotracheal tube using premedication, which has often included opiate analgesia; subsequently, the infant has been ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…While our group had published the local use of higher volume surfactant [ 1 ], this national data support that the MIST procedure may be successfully used regardless of the surfactant volume. Similar to previous survey-based studies, premedication prescription in MIST use remains a highly variable practice and future research exploring ideal agents is needed [ 18 ]. Furthermore, the relative popularity of video laryngoscope use was a notable finding.…”
Section: Discussionmentioning
confidence: 89%
“…While our group had published the local use of higher volume surfactant [ 1 ], this national data support that the MIST procedure may be successfully used regardless of the surfactant volume. Similar to previous survey-based studies, premedication prescription in MIST use remains a highly variable practice and future research exploring ideal agents is needed [ 18 ]. Furthermore, the relative popularity of video laryngoscope use was a notable finding.…”
Section: Discussionmentioning
confidence: 89%
“…The ideal drug would suppress pain and discomfort, while maintaining cardiorespiratory stability and having a minimal impact on the respiratory drive. Moreover, it would allow a rapid onset and offset and be safe in the long term [6, 14, 33]. To optimize the effect of the chosen drug, the time interval before procedure varies according to its pharmacokinetics properties.…”
Section: Discussionmentioning
confidence: 99%
“…An important limit is the need to maintain cardiorespiratory stability and to have a minimal impact on the respiratory drive centres. Spontaneous breathing is considered important during LISA procedure to assure the surfactant dispersion from the trachea and to allow the infant to stay on CPAP [5, 6]. The first large RCT, the Avoidance of Mechanical Ventilation study [18], investigating LISA allowed for sedation at the discretion of the caregiver.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal exposure to painful stimuli at a critical time of brain development in preterm infants is known to be associated with long-term problems such as the decreased development of white matter and subcortical gray matter and chronic pain states in graduates of neonatal intensive care. 71, 122-126 Perlman 126 and Volpe 127 showed that routine endotracheal suctioning changes cerebral blood flow, suggesting that this is a stressful procedure for the infant. Grunau 128 suggests that pain and stress may not only hinder body and head growth but may also cause poor brain development, reduced pain thresholds, and disruption of the set points of biological circuits.…”
Section: Pain Management During Srtmentioning
confidence: 99%
“…And since respiratory depression is an indication for tracheal intubation, usage of sedation can prove to be counterproductive. 122…”
Section: Pain Management During Srtmentioning
confidence: 99%